Biodegradation of additive PHBV/PP-co-PE films buried in soil - Rani-Borges, Barbara [UNESP]; Faria, Adriano Uemura [UNESP]; De Campos, Adriana; Gonçalves, Suely Patricia Costa [UNESP]; Martins-Franchetti, Sandra Mara [UNESP] (FapUNIFESP (SciELO), 2016)
There is considerable concern about the impact plastic materials have on the environment due to their durability and resistance to degradation. The use of pro-oxidant additives in the polymer films could be a viable way to decrease the harmful effects of these discarded materials. In this study, films of PHBV/PP-co-PE (80/20 w/w) and PHBV/PP-co-PE/add (80/19/1 w/w/w) (with pro-oxidant additive) were employed to verify the influence of the additive on the biodegradation of these films in the soil. These films were obtained by melting the pellets in a press at 180 °C which were buried in soil columns for 3 and 6 months. Some samples were also heated before being buried in soil. The biodegradation is higher for the additive blend buried for 3 months than for the pre-heated blend. After 6 months the blend buried and heated/buried was completely degraded in soil. The effect of the additive, on chain oxidation, is more time-dependant than heat-dependant.
Keywords: Additive; Biodegradation; Blend; PHBV/PP-co-PE; Soil